Improved SIC-SVD Hybrid Precoding Algorithm for Indoor Sub-THz Systems - Hang Gui; Yuanyuan Xie; Qingheng Song; Yingjing Qian; Renmin Zhang (IEEE Access, 2023)
Emerging terahertz (THz) communication will become the main way of wireless communication in the future, it will also use hybrid precoding which combines analog and digital hybrid precoding like millimeter wave communication systems, to reduce the system energy consumption. Indoor as a main scenario for communication, to better meet the demands for data transmission. In this paper, an improved hybrid precoding method based on successive interference cancelation and singular value decomposition (SIC-SVD) is proposed for indoor Sub-THz communication system with sub-connected structures. However, the introduction of phase shifters imposes constant modulus constraints, making the problem of hybrid precoding difficult to solve directly. The proposed method first decomposes the optimization problem of achievable rates for the system, based on the special structure of sub-connected, into a series of equivalent sub-problems. The algorithm first designs the analog precoding matrix according to the SIC method, after obtaining the designed analog precoding matrix, the algorithm defines an equivalent channel and employs singular value decomposition (SVD) to obtain the digital precoding matrix. The simulation results show that compared with the existing method based on SIC, the proposed algorithm has slightly higher achievable rate and is closer to the optimal full-digital precoding method. At the same time, this paper also presents a simple analysis of the proposed algorithm for imperfect channel state information (CSI) with different accuracy. Simulation results show that the spectral efficiency is also very near to the perfect CSI case when the accuracy of the CSI is 0.9.